Pengaruh Motivasi Kerja, Kompensasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan Universitas Muhammadiyah Surakarta - Putri, Ferdhina Astia, Drs. Agus Endro Suwarno, M.Si (2016)
The purpose of this research to proof and analyze the influence of work motivation, compensation and work discipline on employees performance at University of Muhammadiyah Surakarta. This research using 76 employees for sampel and taken by convenience sampling method. Convenient sampling is choosing sampel freely according encountered. The data analysis in this research uses SPSS version 17. To examine and prove the research hypothesis so The analysis method that is used is multiple linear regression. result of this research showed that work motivation and work discipline have a significant effect on employee performance. This can be seen from the value tcount >ttabel. But compensation didn't have influence on employee performance. This can be seen from the value tcount < ttabel.